ĐÁNH GIÁ KẾ HOẠCH XẠ TRỊ TOÀN NÃO BẢO TỒN HỒI HẢI MÃ BẰNG KỸ THUẬT XẠ TRỊ ĐIỀU BIẾN LIỀU TRÊN PHẦN MỀM MONACO TẠI BỆNH VIỆN UNG BƯỚU NGHỆ AN (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the quality of hippocampal-avoidance whole-brain radiotherapy (WBRT-HA) treatment plans using intensity-modulated radiotherapy (IMRT) at Nghe An Oncology Hospital.Subjects and Methods: This retrospective descriptive study included 31 radiotherapy treatment plans from 31 patients with brain metastases treated with WBRT-HA between January 2021 and December 2025. Treatment plans were generated using the Monaco treatment planning system with 6 MV photon beams, the Monte Carlo dose calculation algorithm, and a prescribed dose of 30 Gy delivered in 10 fractions. Evaluated dosimetric parameters included PTV coverage (V95%, D98%, and D2%), homogeneity index (HI), conformity index (CI), doses to the hippocampus and organs at risk, monitor units (MU), and beam delivery time.Results: All treatment plans met the prescribed dose distribution criteria, with the mean dose (Dmean) and maximum dose (Dmax) to the PTV of 30.4 ± 0.7 Gy and 33.8 ± 0.8 Gy, respectively. The V95%, D98%, and D2% values were 96.4 ± 1.8%, 28.5 ± 0.8 Gy, and 32.7 ± 0.7 Gy, respectively. The mean HI and CI were 0.14 ± 0.03 and 0.78 ± 0.05, respectively. The mean and maximum hippocampal doses were 9.8 ± 1.2 Gy and 16.8 ± 0.9 Gy, respectively, meeting the RTOG 0933 dose constraints. The maximum dose to both lenses was below 6 Gy. The average number of monitor units was 1794 ± 380 MU, with a mean beam delivery time of 179.4 ± 38 seconds.Conclusion: IMRT enables the development of hippocampal-avoidance whole-brain radiotherapy (WBRT-HA) plans that meet the RTOG 0933 dose constraints, provide adequate target volume coverage, and reduce radiation dose to the hippocampus and other organs at risk. These findings demonstrate the feasibility of this technique for treatment planning using the Monaco treatment planning system.
Keywords: Radiotherapy, Hippocampal-avoidance whole-brain radiotherapy; WBRT-HA; IMRT; hippocampus.